Leading names in education: Claudio Antonio Moyano y Samaniego (Journal of Parents and Teachers, 2013)
Claudio Moyano, politician of the 19th century, is one of the most acknowledged and remembered persons in the contemporary Spanish history of education. Even though he was not involved in pedagogy while he was minister of Development in the government of Ramón Narváez, he promoted a law of public Instruction called Ley Moyano in 1857. This was the law used for 113 years until the General Education Law of 1970. Throughout his professional life, he took part in the Cloister of the Central university of Madrid, as well as in other managerial organs in provincial and national levels in Spain.
Keywords: Leading names in education; Claudio Moyano; General education law; Education.